Uranium-series dating of corals in situ using laser-ablation MC-ICPMS - Potter, E; Stirling, C; Wiechert, U; Halliday, A; Spotl, C (2005)
The in situ U-series dating of corals has been achieved using laser-ablation multiple-collector inductively coupled plasma mass spectrometry (LA MC-ICPMS). Utilising a 193 nm excimer laser coupled to a Nu Instruments Nu Plasma equipped with multiple ion counters, percent-level analytical precision for 234U/ 238U and 230Th/ 238U is obtained. Approximately 70 μg of carbonate is consumed during each analysis, containing approximately 0.2 ng of 238U, ∼10 pg of 234U and less than 3 fg of 230Th. A two-cycle, fast magnet jumping procedure is adopted. In the first cycle 238U is measured in a Faraday collector while the low-abundance isotopes 234U, 232Th, and 230Th are measured simultaneously in ion counters. In the second cycle 235U is measured in an ion counter. All samples are bracketed with an isotopically characterised sample to correct for electron multiplier gain and variable elemental fractionation. U-series ages are then calculated from the measured 234U/ 238U and 230Th/ 238U. Here, we demonstrate the applicability of this technique by analysing a series of coral samples that have been previously characterised by conventional thermal ionisation mass spectrometry (TIMS) and solution-nebulisation multiple-collector ICP mass spectrometry. Excellent agreement is obtained with independent age estimates. The samples have varying degrees of preservation and ages ranging between <10 and 600 thousand years (ka). The age uncertainties achieved are ±1 ka at 3 ka and ±7 ka at 125 ka. Therefore the technique can be used to distinguish between major climatic sub-stages throughout the last 140,000 years spanning the last glacial-interglacial cycle, as recorded in coral reef terraces. The laser-ablation U-series results are independent of coral species. U-series age uncertainties are comparable to those attained using α-spectrometry but require ∼10 4 times less sample and no chemical preparation. © 2004 Elsevier B.V. All rights reserved.